A STUDY ON THE HEALTHCARE SERVICE QUALITY EXPECTATION AND PERCEPTION OF PATIENTS - Gizem Zevde Aydın; Elif Dikmetaş Yardan (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
This study was aimed to measure the quality ofhealth services which expected and perceived by adult patients who werereferred to the health institution and to provide feedback to the institution.In the study, the Servqual scale developed by Parasuraman, Zeithaml and Berryin 1985 was used. The study was carried out on adult patients referred to auniversity hospital. The sample size of the study was determined as 552persons. 565 patients participated in the study. Significance level was takenas p <0.05. Participants of the study were examined for their participationin the questionnaires and it was found that the perceptions of the quality ofthe health services of the patients differ from the Servqual scalesub-dimensions in terms of tangibles, responsiveness, assurance and empathy. Itwas also found that the expectations did not differ according tosub-dimensions. It is proposed that the institution should consider customerexpectations for the quality perception in healthcare services and make the necessarychanges as much as possible in the areas where the expectations are notprovided.